ORIGIN OF CRYSTALLOGRAPHIC TILT IN INGAAS/GAAS(001) HETEROSTRUCTURE - KANG, JM; SON, CS; KIM, MS; KIM, Y; MIN, SK; KIM, CS (AMER INST PHYSICS, 1995)
X-ray rocking curve measurements showed a significant crystallographic tilt in relaxed InGaAs layer grown on (001) GaAs. Transmission electron microscopy revealed that the origin of tilt is 60 degrees dislocations generated having Burgers vectors of a same vertical edge component. Calculations using anisotropic elasticity show that this configuration of 60 degrees dislocation array is energetically favorable when the tilt of epilayer is present as to remove the long range stress field induced by the vertical edge components at the interface. (C) 1995 American Institute of Physics.